2007
DOI: 10.1007/s10347-007-0111-7
|View full text |Cite
|
Sign up to set email alerts
|

Modern bivalve shell assemblages on three atolls offshore Belize (Central America, Caribbean Sea)

Abstract: The Belize atolls-Glovers Reef, Lighthouse Reef and Turneffe Islands-show differences in geomorphology, lagoonal depth, bottom sediment, growth of mangroves and sea-grass, exposure to waves and currents as well as in their sedimentation rates and their age. Bivalve shell assemblages in lagoonal areas reflect these geomorphological differences. On each atoll, 32 to 44 recent sediment samples were taken (total number of samples 111) and bivalve shells subsequently identified. The resulting database (32,122 bival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
(16 reference statements)
1
19
0
Order By: Relevance
“…The epifaunal suspension feeder Ctenoides was dominant at lagoonal but only subdominant at offshore sites. This bysally-attached species has previously been recorded primarily in high energy environments (Hauser et al, 2007). Other subdominant species included epifaunal suspension feeders Lima lima, Caribachlamys imbricata, and C. sentis offshore, and Arca imbricata at lagoons, highlighting the prevalence of hard substrata and relatively high plankton productivity in both environments.…”
Section: Bivalvesmentioning
confidence: 53%
See 2 more Smart Citations
“…The epifaunal suspension feeder Ctenoides was dominant at lagoonal but only subdominant at offshore sites. This bysally-attached species has previously been recorded primarily in high energy environments (Hauser et al, 2007). Other subdominant species included epifaunal suspension feeders Lima lima, Caribachlamys imbricata, and C. sentis offshore, and Arca imbricata at lagoons, highlighting the prevalence of hard substrata and relatively high plankton productivity in both environments.…”
Section: Bivalvesmentioning
confidence: 53%
“…Reef environments with higher relative planktonic productivity are likely to host more suspension feeders, while reef environments with high benthic algal productivity can support more herbivores (Russ, 2003). Dominance of epifaunal or boring bivalves is an indication of high (live or dead) coral cover (Hauser et al, 2007;Harries and Sorauf, 2010), while dominance of infaunal bivalves is an indication of high sediment and lower coral cover . Molluscan life habits may also indicate the amount of environmental stress in a reef environment, which can have a natural or anthropogenic source.…”
Section: Mollusks As Environmental Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, if the lagoon's fetch is large enough, and if the geometry of the bottom facilitates it, wind-driven waves inside the lagoon may be an additional and even a dominant circulatory force (e.g., Andréfouët et al, 2001;Montaggioni et al, 2015). There are even a few instances in which lagoons appear to be quite open but nonetheless develop a degree of hypersalinity, as on Glover's, Lighthouse and Turneffe reefs of Belize (Table B.1; Hauser et al, 2007). The main lagoon of Turneffe is 8 m deep and exhibits restricted circulation due to mangrove development (Gischler, 2003).…”
Section: Lagoon Variation: An Abbreviated Overview Of the Atoll Familymentioning
confidence: 99%
“…In the tropics they often represent the most diverse members of reef complexes: one intensive study of an Indo-Pacific coral reef and its associated habitats found 2738 species of marine molluscs in 295 km 2 (Bouchet et al 2002). Detailed surveys of individual reef and seagrass systems frequently reveal 100 species or more (Greenway 1995), and comprehensive compilations reach thousands of species across regions such as the Caribbean (Jackson 1972, Hauser et al 2007, Miloslavich et al 2010. Life habits, feeding modes, reproduction, and life histories vary immensely among different bivalves and gastropods, and combine to form a wide array of functional modes performed by molluscs (Todd 2001).…”
mentioning
confidence: 99%